Improvment the competitiveness of the real estate agency services: 5 basic principles - I. A. Prudnikov; A. M. Rotar (Путеводитель предпринимателя, 2020)
In the context of transformation of the service sector, many statements have already been made that the market of real estate services is waiting for an imminent demise and oblivion. However, the European and American market with its «saturation» of the market shows the opposite, the market of real estate services is also transformed and varies depending on the needs of customers. If initially real estate services operated on the principle of «buy-sell», now real estate agencies can help in renting an apartment, organize cleaning of real estate, provide services for maintenance of premises, etc. The market forces many service industries to change and the market poses new challenges to its participants. The article analyzes the current state of Affairs of real estate business, as well as practical examples of its development.